Leginon: New features and applications. (3rd November 2020) - Cheng, Anchi; Negro, Carl; Bruhn, Jessica F.; Rice, William J.; Dallakyan, Sargis; Eng, Edward T.; Waterman, David G.; Potter, Clinton S.; Carragher, Bridget
Abstract: Leginon is a system for automated data acquisition from a transmission electron microscope. Here we provide an updated summary of the overall Leginon architecture and an update of the current state of the package. We also highlight a few recent developments to provide some concrete examples and use cases.